The nth triangular number is the sum of the first n integers:
1, 1+2=3, 1+2+3=6, 1+2+3+4=10, etc.
It can be proved that the nth triangular number is equal to n(n+1)/2. Call this Tn. Then 2Tn = n(n+1) = n^2 + n, so the n'th square number is equal to twice the nth triangular number minus n.
2006-12-20 19:50:58
·
answer #1
·
answered by Scarlet Manuka 7
·
0⤊
0⤋
Let the square numbers be S_1, S_2, S_3, ... S_n
Where S_n = n²
Let the triangular numbers be T_1, T_2, T_3, .... T_n
Where T_n = 1 + 2 + 3 + .... + n = n/2(n + 1)
Then S_n = T_n + T_(n - 1)
Proof
T_n = n/2(n + 1) = n²/2 + n/2
T_(n - 1) = (n - 1)/2 * ((n - 1) + 1) = n/2(n - 1) = n²/2 - n/2
So T_n + T_(n - 1) = (n²/2 + n/2) + (n²/2 - n/2)
= n²/2 + n/2 + n²/2 - n/2
= n²
= S_n .... QED
Example:
Square numbers are {1, 4, 9, 16, 25, 36, 49, 64, .......}
Triangular numbers are {1, 3, 6, 10, 15, 21, 28, 36, ......}
Sum af 1st two Triangular numbers is 4 = S_2
T_5 + T_6 = 15 + 21 = 36 = S_6 etc The sum of any two consecutive triangular numbers results in a square number.
2006-12-21 05:32:44
·
answer #2
·
answered by Wal C 6
·
1⤊
0⤋
4 is kind of triangular. 5 is more square. (this part is kind of advanced, but try to follow: 8 is round)
2006-12-21 03:52:43
·
answer #3
·
answered by sarah e 1
·
0⤊
0⤋